NeuroFusion-ViT: A Hybrid CNN-EVA Transformer Model with Cross-Attention Fusion for MRI-Based Alzheimer's Stage Classification - Soylemez, Derya Ozturk; Dogru, Sevinc Ay (Mdpi, 2026)
Background: Alzheimer's disease is the most common type of dementia and a progressive neurodegenerative disease that begins with neuronal damage and leads to a reduction in brain tissue. Currently, there is no cure for this disease, and existing approaches focus on alleviating symptoms. Methods: This study proposes NeuroFusion-ViT, a highly accurate and computationally efficient hybrid deep learning model for early-stage detection of Alzheimer's disease. The model combines an EVA-02-based Vision Transformer (ViT) with the ConvNeXt-Small CNN architecture, providing powerful representation learning that can process both global context and local details. The proposed Gated Cross-Attention Fusion (G-CAF) mechanism dynamically combines two different features, offering high discriminative power and model stability. Results: In experiments conducted on the OASIS MRI dataset, the model achieved 99.86% accuracy, 0.9989 Macro F1, and 0.999 ROC-AUC values, demonstrating clear superiority over single-modal and hybrid models described in the literature. Furthermore, 5-fold cross-validation results also support the model's high generalizability. Ablation studies showed that each of the components-cross-attention, gate mechanism, Dual LayerNorm, and FFN-Dropout-made a meaningful contribution to performance. Conclusions: The results demonstrate that the NeuroFusion-ViT architecture offers a reliable, stable, and clinically applicable solution for Alzheimer's stage classification.
Keywords: Alzheimer; vision transformers; MRI